PEMBERDAYAAN POKDARWIS DI WISATA SUNGAI TROKON DESA CAWANG LAMA REJANG LEBONG PROVINSI BENGKULU - Farahdila, Nuriskita; Gusti, Ririn; Ulfasari, Nia (Comm-Edu (Community Education Journal), 2025)
This study aims to analyze the strategy of the Tourism Awareness Group (POKDARWIS) in mobilizing the community to actively participate in the development and management of Trokon River tourism in Cawang Lama Village, Rejang Lebong Regency, Bengkulu. The research technique used is descriptive qualitative with data collection techniques through observation, interviews, and documentation. The results of the study indicate that POKDARWIS implements a community empowerment strategy through tour guide training, lodging management, local product processing, and the formation of community-based business groups. Although this strategy has received community support, challenges remain, especially in terms of understanding the concept of sustainable tourism and limited infrastructure. For this reason, POKDARWIS collaborates with the community and ensures the sustainability of tourism. This study concludes that community participation is very important in the development of tourism based on local wisdom, and that collaborative and participatory mobilization strategies are the key to its success.